2019
DOI: 10.1002/bkcs.11697
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Methylene Blue on RuO2–CNT

Abstract: Photodegradation of organic pollutants by oxide-based photocatalysts has gained increasing attention as a solution to environmental problems. Generally, the degradation of pollutants proceeds by reaction with reactive hydroxyl radicals, which are generated by the reaction of water molecules adsorbed onto the photocatalyst with photogenerated charge carriers on the surface of the photocatalyst. 1,2 However, the fast recombination rate of photogenerated charge carriers limits the ability to enhance the photocata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…This approach was consistent with previous work on MB decontamination in aqueous media, and, additionally, as a reliable test since MB dye was also commonly used to test photocatalytic ability of nanohybrids. [68][69][70][71][72] Colorimetric observations showed that upon oxidation, this common dye and notorious pollutant, MB turns from blue to colourless, thus providing a qualitative response on its annihilation and removal from solution phase. We observed a similar feature in the presence of GO or ZnBTSC2@GO even in the absence of violet light irradiation (Fig.…”
Section: And Esi †)mentioning
confidence: 99%
“…This approach was consistent with previous work on MB decontamination in aqueous media, and, additionally, as a reliable test since MB dye was also commonly used to test photocatalytic ability of nanohybrids. [68][69][70][71][72] Colorimetric observations showed that upon oxidation, this common dye and notorious pollutant, MB turns from blue to colourless, thus providing a qualitative response on its annihilation and removal from solution phase. We observed a similar feature in the presence of GO or ZnBTSC2@GO even in the absence of violet light irradiation (Fig.…”
Section: And Esi †)mentioning
confidence: 99%